Scalar implicatures in Chinese children with reading difficulties. Issue 5 (October 2019) - Hu, Shenai; Zhou, Peng; Foppolo, Francesca; Vender, Maria; Delfitto, Denis
This study investigates the derivation of scalar implicatures in Chinese children with reading difficulties (RD). Twenty-four children with RD (mean age 9 years and 8 months), 20 age-matched typical readers (mean age 9 years and 10 months), 20 six-year-old children and 20 five-year-old children were tested with the comprehension of sentences with scalar items yixie 'some' and suoyou 'all'. The pattern of children with RD was similar to that of six-year-old children but differed from that of age-matched typical readers in the comprehension of the sentences containing yixie that were pragmatically underinformative in the context. Interestingly, many children with RD and younger children, who accepted the sentences containing yixie that were pragmatically underinformative, rejected the sentences containing yixie that were true in a context supporting the literal (semantic) interpretation. These results support the view that the computation of scalar implicatures may be impaired in children with RD, due to a complex interplay of factors such as (at least) the lexical knowledge of the scalar term and processing/pragmatic limitations.